Why war fails: Russia$1 (Bs invasion of Ukraine and the limits of military powers - Lawrence, Freedman (Foreign Affairs)
On February 27, a few days after Russia invaded Ukraine, Russian forces launched an operation to seize the Chornobaivka airfield near Kherson on the Black Sea coast. Kherson was the first Ukrainian city the Russians managed to occupy, and since it was also close to Russia$1 (Bs Crimean stronghold, the airfield would be important for the next stage of the offensive. But things did not go according to plan. The same day the Russians took over the airfield, Ukrainian forces began counterattacking with armed drones and soon struck the helicopters that were flying in supplies from Crimea. In early March, according. Reproduced s